From war material culture to popular heritage, and beyond: The “PSP - cancelli di Venosa” as paradigms of object biography theory - García Sánchez, Jesús (Ex Novo: Journal of Archaeology, 2018)
Using object biography and Behavioral Archaeology as main theoretical frameworks this paper will examine how the pierced steel planks (PSP), also called Marston mat, become cancelli di Venosa (Venosa’s doors) within the social context where they happen to be located – in the immediate surroundings of Venosa airfield in this casestudy – where several actions occur such as reclamation, re-crafting, functional change, etc. These objects’ biography is, however, not restricted to this study area since they were used widely in the Second World War thus the paper aims to assess their geographical and chronological evolution. Furthermore, I will focus on the modern day utilization of the PSP-cancelli di Venosa and their promotion to the category of local heritage, a phenomenon often termed as heritagization, and their agency in the reproduction of war ideology and imperialistic narratives in Twentieth century popular culture.